Filosofia da educação: limites e possibilidades na formação do pedagogo - SOARES, Raimunda Lucena Melo (Universidade Federal do Pará, 2012)
The present work is on the Philosophy of Education, from the standpoint of its limitations and possibilities, as practical and theoretical activity that focuses on educational problems. The Philosophy of Education in educator’s formation may consist of either a solution to educational problems, because of its critical perspective as a problem especially if it does not recognize its own limits. Thus, the problem that drives this study relates to the limits of the discipline Philosophy of Education in the pedagogue formation and the issues that guide the investigations made here are: What possibilities and limits does the Philosophy of Education have in pedagogue training? Where can we place them? What the Brazilian theorists say about the Philosophy of Education? And this, as a subject, as conceived by its teachers and students at the School of Education? With the main goal of analyzing the participation of Philosophy of Education, its limits and possibilities in educator formation, asking in which environments we can place them in order that this discipline is a set of knowledge linked to two major areas of knowledge: Philosophy and Education, in their complexities, contradictions and connections were chosen as the main source of research works of authors who conceive education as a social-historical process, philosophy and the philosophy of education in their specific critical and reflective, as well as the teachers and students of the Faculty of Education testimony from the Federal University of Pará, Pará State University and University of Amazonia, in the 1990s, which gave interviews about the epistemological interest of this study. The data analysis allowed to observe that the limits, but also the possibilities of the discipline Philosophy of Education are made in the relations among Philosophy of Education and Education, Philosophy, and educational practice of teachers and students and the contradictions made into these theoretical and practical context areas of knowledge, according to the needs and contingencies to which they are subjected in social and historical context.